Minimally Invasive Peroneal Tenodesis Assisted by Peroneal Tendoscopy: Technique and Preliminary Results - Rodrigo Simões Castilho; João Murilo Brandão Magalhães; Bruno Peliz Machado Veríssimo; Carlo Perisano; Tommaso Greco; Roberto Zambelli (Medicina, 2024)
Introduction: Peroneal disorders are a common cause of ankle pain and lateral instability and have been described in as much as 77% of patients with lateral ankle instability. Clicking, swelling, pain, and tenderness in the peroneal tendons track are frequent symptoms, but they can be confused with other causes of lateral ankle pain. The management of peroneal disorders can be conservative or surgical. When the conservative treatment fails, surgery is indicated, and open or tendoscopic synovectomy, tubularization, tenodesis or tendon transfers can be performed. The authors present a surgical technique of tendoscopy associated to minimally invasive tenodesis for the treatment of peroneal tendon tears, as well as the preliminary results of patients submitted to this procedure. Methods: Four patients with chronic lateral ankle pain who were diagnosed with peroneal brevis pathology were treated between 2020 and 2022 with tendoscopic-assisted minimally invasive synovectomy and tenodesis. Using a 2.7 mm 30° arthroscope and a 3.0 mm shaver blade, the entire length of the peroneus brevis tendon and most parts of the peroneus longus tendon can be assessed within Sammarco’s zones 1 and 2. After the inspection and synovectomy, a minimally invasive tenodesis is performed. Results: All patients were evaluated at least six months after surgery. All of them reported improvement in daily activities and in the Foot Function Index (FFI) questionnaire (pre-surgery mean FFI = 23.86%; post-surgery mean FFI = 6.15%), with no soft tissue complications or sural nerve complaints. Conclusion: The tendoscopy of the peroneal tendons allows the surgeon to assess their integrity, confirm the extent of the lesion, perform synovectomy, prepare the tendon for tenodesis, and perform it in a safe and minimally invasive way, reducing the risks inherent to the open procedure.